2022
DOI: 10.3390/ma15072400
|View full text |Cite
|
Sign up to set email alerts
|

Application of Machine Learning Approaches to Predict the Strength Property of Geopolymer Concrete

Abstract: Geopolymer concrete (GPC) based on fly ash (FA) is being studied as a possible alternative solution with a lower environmental impact than Portland cement mixtures. However, the accuracy of the strength prediction still needs to be improved. This study was based on the investigation of various types of machine learning (ML) approaches to predict the compressive strength (C-S) of GPC. The support vector machine (SVM), multilayer perceptron (MLP), and XGBoost (XGB) techniques have been employed to check the diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…In comparison, Wang et al [84] also anticipated the CS of geopolymer concrete by using the AdaBoost, random forest, and decision tree algorithms and reported the R 2 value equal to 0.90, 0.90, and 0.83, respectively. Cao et al [86] also employed SVM and MLP approaches for the CS of geopolymer concrete and reported the R 2 result as 0.91 and 0.88, respectively. It also indicates that the selected algorithms in the present study performed better than the approaches used in the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, Wang et al [84] also anticipated the CS of geopolymer concrete by using the AdaBoost, random forest, and decision tree algorithms and reported the R 2 value equal to 0.90, 0.90, and 0.83, respectively. Cao et al [86] also employed SVM and MLP approaches for the CS of geopolymer concrete and reported the R 2 result as 0.91 and 0.88, respectively. It also indicates that the selected algorithms in the present study performed better than the approaches used in the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…[63][64][65][66][67][68][69][70]. Estimations of various characteristics of conventional and advanced concretes, such as durability, thermal characteristics, and mechanical characteristics, have been extensively covered in previous studies [71][72][73][74].…”
Section: Categories Of Machine Learningmentioning
confidence: 99%
“…Some other researchers developed compressive strength predictive models of fly ash based geopolymer concrete (FGPC) using Support Vector Machine (or) Regression (SVM/ SVR) in addition to Random Forest Method, Back propagation neural network, Multilayer perceptron and Extreme gradient boosting algorithm etc. It was concluded that all these models can be effectively employed in the prediction of compressive strength of FGPC [34][35][36].…”
Section: Introductionmentioning
confidence: 99%